Serum leptin and ghrelin concentrations of maternal serum, arterial and venous cord blood in healthy and preeclamptic pregnant women - Aydin, S.; Guzel, S. P.; Kumru, S.; Aydin, Suna; Akin, O.; Kavak, E.; Halifeoglu, I. (Springer, 2008)
Preeclampsia, a common complication of pregnancy, is associated with alteration in the concentration of leptin in maternal blood. The action of leptin is antagonistic to that of ghrelin. Here, we compared the levels of leptin and ghrelin in maternal serum and in arterial and venous cord blood between healthy pregnant women and those suffering from mild and severe preeclampsia. The levels of leptin in maternal and newborn's blood were elevated in both mild and severe preeclamptic patients (p<0.05). Moreover, serum ghrelin levels were negatively correlated with blood pressure and leptin/ghrelin ratio was decreased in preeclampsia (p<0.05). We concluded that increased production of ghrelin may represent a compensatory hypotensive mechanism in preeclamptic women.
Keywords: leptin; ghrelin; pregnancy; hypertension